Characterization of the recombinant proteins Ser 3 and BARN - Karl, Lorenz (Jihočeská univerzita, 2020)
This bachelor thesis deals with the expression of two recombinant proteins in a bacterial expression system. These proteins are derived from adhesive proteins originating from silkworm (Bombyx mori) silk and cement from barnacle (Megabalanus rosa). This thesis includes optimization of the protocol for protein expression and simple characterization of recombinant proteins involving examination of its biocompatibility in tissue culture and ability to form films on different substrates using electron microscopy.
Characterization of the recombinant proteins Ser 3 and BARN